An innovative teaching approach to encourage creative and entrepreneurial mindset among students: the case of Smart Financial Statement Card (SFSC) / Hasni Abdullah ... [et at.] - Abdullah, Hasni; Khalid, Khairi; Md Yusof, Norhidayah; Ahmad, Badli Esham; Abd Rahman, Muhammad Zahran (2018)
An entrepreneurial mindset is not only focused on contributing to the economy, yet it is also important in creating and developing products, services, technologies and solutions to problems that can be beneficial to the society. Thus, it is important to instill this mindset not only among the entrepreneurs but for everybody and in this context among the students. Therefore, in order to in stil this entrepreneurial mindset among the students, the teachers need to be innovative and employ this entrepreneurial mindset in order to entice the students to be actively involved in class while instilling this entrepreneurial mindset in them. In order to achieve this, students' involvement in class should be one of the powerful factors as it will lead to the improvement of the teaching quality especially in higher education institutions. Thus, having better students involvement could lead to success in teaching them. Therefore, the aim of this article is to introduce an innovative teaching approach by using smart flashcard which is the Smart Financial Statement Card or known as SFSC. It is believed the SFSC can be considered as an innovative teaching approach which employs a process of inculcating entrepreneurial mindset which could help simplifying the process of teaching and learning in finance class. In addition, SFSC is believed to be able to enhance the students' achievement when the teachers use this for teaching and learning purposes. Thus, the preliminary investigation was conducted to study the eff ects of using smart flashcards on two different groups of students which are control and experimental groups. This is done in order to know how efficient this innovative teaching approach could be. Based on the results of independent t-test, there is a significant difference in results for students without smart flashcard (control group) and students with smart flashcard (experimental group). It can be seen that students with smart flashcard (experimental group) scored much higher as compared to students without smart flashcard (control group). Besides that, this preliminary result suggests that the teachers are supposedly willing to foster quality teaching by utilizing smart flashcard as an interactive and innovative teaching approach in their teaching process. The result shows how creativity and innovation as well as entrepreneurial teaching approach contribute to the effective of teaching and learning process.